Correlation of Uric Acid Levels with Lipid Profile among MCU Patients - Hidayah, Aghnia; Ciptono, Freddy (Fakultas Kedokteran Universitas Kristen Krida Wacana, 2025)
Introduction: Uric acid (C5H4N4O3) is a product of purine degradation and can act as a pro-oxidant substance because of the formation of ROS through the enzymatic activity of xanthine oxidase. Previous research has shown that uric acid can affect lipid metabolism in the body. Purpose: This study aims to explore the relationship between lipid profiles in MCU patients and uric acid levels. This study employs a cross-sectional design, and we will analyze the data using linear regression. Methods: This study is an observational analytic study without intervention, using a cross-sectional study design. The research data came from secondary data, especially the medical records of MCU patients. Researchers selected the study sample using a random sampling technique. The study uses 86 secondary data samples. Results: Linear regression analysis reveals a significant positive correlation between uric acid and triglycerides (p-value < 0.001 and r = 0.464), total cholesterol (p-value = 0.018 and r = 0.255), and LDL (p-value = 0.011 and r = 0.273). A significant negative correlation exists between uric acid levels and HDL (p-value < 0.001 and r = 0.477). Increased uric acid levels are associated with higher levels of TG, TC, and LDL, as well as a decrease in HDL levels. The average levels of LDL and total cholesterol are 140.27 mg/dl and 206.66 mg/dl, respectively, which are at the high threshold, while all other variables are within normal limits. Conclusion: This study concludes that uric acid levels and lipid profile levels are significantly related